2009
DOI: 10.1007/s12011-009-8391-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gestational Cadmium Exposure on Pregnancy Outcome and Development in the Offspring at Age 4.5 Years

Abstract: The objective of the present study was to evaluate the potential effect of maternal cadmium exposure on pregnancy outcome and development in the offspring at age 4.5 years. Between November 2002 and December 2003, 109 normal pregnant women were enrolled in our cohort from Da-Ye Country, Hubei Province in Central China. The placental, whole blood, and cord blood levels of cadmium were determined by inductively coupled plasma mass spectrometer (ICP-MS). The 106 children at 4.5 years of age given birth by the afo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
85
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(91 citation statements)
references
References 27 publications
4
85
1
1
Order By: Relevance
“…Other studies have found adverse associations of maternal B‐Cd with SGA and/or birthweight in models adjusted for smoking 14, 15, 16. Conversely, other studies have found no associations7, 9, 12, 30 or even beneficial associations31 with birthweight or SGA in models adjusted or stratified for smoking, even when mean or median maternal B‐Cd levels were high (>1 μg/L) 10, 32, 33. There is greater consensus for other birth outcomes (birth length or crown–heel length, head circumference, gestational age, preterm birth), with most studies finding no associations (see Table S5).…”
Section: Commentsmentioning
confidence: 98%
“…Other studies have found adverse associations of maternal B‐Cd with SGA and/or birthweight in models adjusted for smoking 14, 15, 16. Conversely, other studies have found no associations7, 9, 12, 30 or even beneficial associations31 with birthweight or SGA in models adjusted or stratified for smoking, even when mean or median maternal B‐Cd levels were high (>1 μg/L) 10, 32, 33. There is greater consensus for other birth outcomes (birth length or crown–heel length, head circumference, gestational age, preterm birth), with most studies finding no associations (see Table S5).…”
Section: Commentsmentioning
confidence: 98%
“…NCC give rise to rib cage (Henderson et al, 1999); (1) (Grandjean et al, 1997); (2) (Grandjean and Landrigan, 2006); (3) (Opler et al, 2008); (4) (Ha et al, 2009); (5) (Tian et al, 2009); (6) (Kippler et al, 2012); (7) (Hamadani et al, 2011); (8) (Saha et al, 2012); (9) (Eubig et al, 2010); (10) (Patandin et al, 1999); (11) (Valvi et al, 2012); (12) (Lai et al, 2002); (13) (Chen et al, 1992); (14) (Zarn et al, 2004); (15) (Di Renzo et al, 2007); (16) (Machera, 1995); (17) (Giavini and Menegola, 2010); (18) (Krieger, 2004); (19) (Dean et al, 2002); (20) (Arndt et al, 2005); (21) (Meador et al, 2006); (22) (Rasalam et al, 2005); (23) (Menegola et al, 2005b); (24) (Verbois, 2006); (25) (Valenzuela-Fernandez et al, 2008).…”
Section: Biostatistics and Data Display Algorithmsunclassified
“…It is important to say that these results were based on the hair Cd analysis in children, which may be subject to external contamination. In a more recent study, the effects of maternal exposure in the offspring were assessed by measuring cord blood Cd levels that present the absolute amount of metal that reaches the fetus through the placenta (Tian et al 2009). Tian et al (2009) reported an IQ full score of children in the higher cord blood cadmium group that was significantly lower with respect to the controls.…”
Section: Neurotoxic Effectsmentioning
confidence: 99%
“…In a more recent study, the effects of maternal exposure in the offspring were assessed by measuring cord blood Cd levels that present the absolute amount of metal that reaches the fetus through the placenta (Tian et al 2009). Tian et al (2009) reported an IQ full score of children in the higher cord blood cadmium group that was significantly lower with respect to the controls. Moreover, cadmium concentration in urine (that may be used as a biomarker of exposure in early pregnancy), even at low doses, was associated to decreased IQ scores in children (Kippler et al 2012a).…”
Section: Neurotoxic Effectsmentioning
confidence: 99%